Cerebrovascular ultrasound in stroke prevention and treatment - Alexandrov, Andrei V.; Wiley InterScience (Online service) (Oxford ; Hoboken, NJ : Wiley-Blackwell, 2011)
"Cerebrovascular Ultrasound in Stroke Prevention and Treatment, Second Edition, assists neurologists, radiologists, and ultrasonographers in stroke therapy by providing practical approaches to the examination of patients, the interpretation of ultrasound studies, and the application of cerebrovascular ultrasound in the development of management and treatment studies. Full-color images and case studies add to the book's appeal."--Provided by publisher.
Machine generated contents note: Title: Cerebrovascular Ultrasound in Stroke Prevention and Treatment. Editor: Andrei V. Alexandrov, MD. Contents: Foreword Werner Hacke Part I. How To Perform Ultrasound Tests? Principles of Extracranial Ultrasound and Examination Techniques Alice Robinson-Vaughn, Marta Rubiera, M. Neumyer, A. Alexandrov (edits pending). Principles of Intracranial Ultrasound and Examination Techniques Marta Rubiera, Alice Robinson-Vaughn, A. Alexandrov, M. Neumyer (edits pending). Anatomy of Pre-Cerebral Vessels and the Circle of Willis Joel Cure (received). Part II. Hemodynamic Principles. Integrated Assessment of Systemic and Intracranial Hemodynamics A.W. Alexandrov (confirmed). Practical Models of Cerebral Hemodynamics and Waveform Recognition R. Aaslid (received), A. Alexandrov. Part III. Criteria for Interpretation. Diagnostic Criteria for Neurovascular Studies G. Tsivgoulis (confirmed), A. Alexandrov, M. Neumyer. Part IV. Ultrasound in Stroke Prevention and Treatment. Sickle Cell Disease F. Nichols (confirmed), A. Jones, R. Adams. Cardiovascular Risk Factors and Carotid Ultrasound T. Rundek (confirmed), J. Polak. Secondary Prevention and Stenting J. Kim (confirmed), C. Tegeler, D. Ratanakorn. Acute Ischemic Stroke R. Mikulik (received revised), A. Demchuk, A. Alexandrov. Vasospasm after SAH M. Harrigan (received, revised, new figures pending), D. Newell, A. Alexandrov. Part V. Select Clinical Applications and Clinical Vignettes. Ultrasound in Neuro-critical care A. Barreto (received revised), J. Grotta. Carotid duplex -- beyond percent stenosis John Pellerito (confirmed). Intracranial Disease Vijay Sharma (received revision pending), L. Wong. Detection of right-to-left shunts A. Lao (done), J. Jesurum. Vasomotor reactivity and reversed Robin Hood Syndrome G. Tsivgoulis, Marta Rubiera (to be done in August). Intra-operative monitoring Z. Garami (confirmed), A. Lumsden. Imaging and monitoring reperfusion therapies C. Molina, P. Schellinger (confirmed). Ultrasound and microspheres F. Forsberg (received revision pending).
Includes bibliographical references and index.
Print version record.
Keywords: Cerebrovascular disease -- Ultrasonic imaging; Stroke -- ultrasonography; Stroke -- diagnosis; Stroke -- therapy; MEDICAL -- Neurology; Cerebrovascular disease -- Ultrasonic imaging; Electronic books